Development of new aromatase inhibitors analogues of letrozole: perspectives for treatment of male infertility - Coelho, Anaísa Nascimento (2016)
Nowadays, infertility is one of the major health issues. Human fertility depends on several psychological, physical and biochemical factors, with a successful spermatogenesis being the fundamental basis for male fertility. The male sexual function and the proper development of spermatogenic process are highly dependent on the hormonal regulation, particularly by the actions of sex steroid hormones, androgens and estrogens. 17ß-Estradiol (E2), the metabolite of testosterone (T) aromatization by the activity of aromatase, is the most potent estrogen produced in the human body. Aromatase is a member of the cytochrome P450 protein superfamily that regulates the last step of estrogen biosynthesis, aromatizing the A-ring of androgens such as T and androstenedione into E2 and estrone, respectively. Thus, in men, E2 is responsible for a number of effects originally attributed to T. On the other hand, men with a high serum E2/T ratio are infertile and it has been suggested that they can be treated with aromatase inhibitors (AIs). Indeed, AIs have been shown to increase T levels, and restore spermatogenesis, in infertile men with this endocrinopathy. Among other classes of compounds, letrozole is a nonsteroidal AI that has been widely used for treatment of male infertility. In order to develop more selective and efficient AIs, letrozole analogues were synthesized, where one of the rings of benzonitrile was substituted by a phenyl group in para position with different functional groups, and the methine bridge was substituted by a vinyl group. Furthermore, their reduced congeners were synthesized. Overall, the synthesis of nine letrozole analogues was performed. To the best of our knowledge, six letrozole analogues were reported for the first time in this dissertation. All compounds were structurally characterized with prominence by nuclear magnetic resonance spectrometry. Additionally, aromatase docking studies were performed. Giving the resemblance between all the letrozole analogues synthesized, it was not surprising that the results were very similar. The simulation revealed that the compounds in this study showed higher affinity to the enzyme, when compared with letrozole. After the synthesis, purification and characterization steps, two representative letrozole analogues namely 4-(2-phenyl-1-(1H-1,2,4-triazol-1-yl)vinyl)benzonitrile and 4-(2-phenyl-1-(1H-1,2,4-triazol-1-yl)ethyl)benzonitrile were selected for evaluation of their biological activity as potential AIs in testicular cells. For this purpose, rat seminiferous tubules (SeT) were cultured ex vivo in the presence or absence of 200 nM or 400 nM of letrozole and the vinyl and ethyl letrozole analogues. Steroid hormone production, the tubular differentiation index (TDI) and the glycolytic metabolism were evaluated. The synthesized letrozole analogues, which were selected for biological evaluation as potential AIs, seem to suppress glycolytic metabolism. On the other hand, letrozole increased the metabolizing of glucose with augmented production of lactate. Relatively to the TDI, it was significantly reduced in the SeT exposed to letrozole 200 nM and ethylbenzonitrile letrozole analogue both in 200 nM and 400 nM. However, no dose-dependent relationship was observed for the AIs under study. Moreover, without the radioimmunoassays results for quantifying T and E2 in the culture medium, it is not possible to advance a definitive conclusion about the distinct behavior of letrozole and its analogues studied in this dissertation. Nevertheless, considering the effects observed on TDI and glycolytic metabolism, only with 24 h of culture, it is possible to conclude that both letrozole analogues are biologically active. In the future, it would be of uttermost importance to evaluate the biological activity of the remaining synthesized compounds as AIs in testicular cells.